Can cadaverous pollution from environmental lead misguide to false positive results in the histochemical determination of Gunshot Residues? In-depth study using ultra-sensitive ICP-MS analysis on cadaveric skin samples. (November 2018) - Boracchi, Michele; Andreola, Salvatore; Collini, Federica; Gentile, Guendalina; Lucchini, Giorgio; Maciocco, Francesca; Sacchi, Gian Attilio; Zoja, Riccardo
Highlights: Environmental contamination by lead. ICP-MS sensitivity. Gunshot Residues on corpses. Abstract: Introduction: In a previous work, we wanted to evaluate if the histochemical determination of lead in Gunshot Residues (GSR) on firearm wounds could be misled due to possible environmental contamination produced by heavy metals and, in particular, by lead. The Sodium Rhodizonate test and its confirmation test with 5% HCl Sodium Rhodizonate resulted to be negative and therefore we wanted to verify if these techniques were sensible enough in order to evaluate this element. We have assessed, on these same samples, a more sensitive technique, as inductive coupled plasma mass spectrometry (ICP-MS) is. This technique is able to detect elements in solution at concentrations as low as 10 −15  g L −1 . Materials and methods: Skin samples taken from two groups of victims, whose cause of death was not related to gunshot wounds were analyzed using ICP-MS: group A included 25 corpses found in open spaces after a long time; group B included 16 corpses exhumed after a period of 11 years. As a positive control group we used skin samples from two subjects that had died due to firearm wounds: as a negative control group we used three different types of plain paraffin slides without included biological material. Results: At the analysis by ICP-MS, the evaluation of the samples belonging to groups A, B and for the negative control groups resulted to be negative for traces of lead (Pb), barium (Ba) and antimony (Sb). On the other hand, high concentrations of GSR could be found in the positive control group were victims died for firearm wounds. Conclusions: On these basis, we can state that environmental Pb does not contaminate cadavers exposed to open air nor those buried in soil, as confirmed using to ICP-MS technique. Sodium Rhodizonate and 5% HCl Sodium Rhodizonate confirmation test have therefore a high sensitivity, highlighting GSRs, for the diagnosis of death caused by firearm wounds.